Structural Characterization of Antennae of Stored Grain Pests (Coleoptera): A Review - Jaswal, Tania; Bali, Gagan Preet Kour (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This review article is aimed at stored grain pests which are a serious threat to global food security. Insect infestations can have a devastating impact on grain facilities, leading to significant economic losses in the agricultural sector. These insects possess sophisticated antennae in their head capsules, which contain numerous sensory receptors and organs. These specialized structures enable the insects to navigate their environment, locate food, seek shelter, find mates, identify breeding sites, and evade predators and other threats. Researchers study the intricate structure of these antennae using advanced techniques such as the scanning electron microscope (SEM). By gaining a deeper understanding of the antennal structure, experts hope to develop more effective strategies to prevent and combat insect damage in storage facilities.